Glutamine in Clinical Nutrition - Rajendram, Rajkumar; Preedy, Victor R.; Patel, Vinood B. (Nutrition and Health,, 2015)
This text is the first published volume for health professionals and advanced students that examines the biochemistry, clinical nutrition, and therapeutic aspects of glutamine. Drs. Rajendram, Preedy, and Patel are experts in their respective fields and have gathered an august list of contributors that represent the medical profession as well as the academic research community. Glutamine in Clinical Nutrition provides a timely, comprehensive, evidence-based review on the literature that presents the application of current nutritional knowledge by physicians and dietitians and incorporates emerging fields of science and important discoveries. Notable topics include coverage on manganese toxicity and the glutamine-glutamate cycle, glutamine supplementation in HIV, glutamine addiction of cancer cells, glutamine supplementation during major surgery and in intensive care, and glutamine concerns with regards to sepsis, trauma, diabetes, and other diseases. The final chapter provides a wealth of information on web-based resources and suggested readings for the health provider. Written by authors of international and national standing, leaders in the field and trendsetters, Glutamine in Clinical Nutrition is essential reading for nutritionists and dietitians, public health scientists, physicians, epidemiologists, policy makers, and health care professionals of various disciplines.